Global food projections to 2020: implications for investment - Rosegrant, Mark W.; Agcaoili-Sombilla, Mercedita C.; Perez, Nicostrato D. (International Food Policy Research Institute, 1995)
This paper examines the global food security picture through 2020, using a model that incorporates 35 individual countries and regions and 17 commodities to estimate supply and demand for food. It concludes that if governments and the international community maintain current levels of commitment to agricultural growth through cost-effective investment in agricultural research, extension, irrigation and water development, human capital, and rural infrastructure, the world as a whole will not experience overwhelming pressure but food security in many developing countries, particularly in South Asia and Sub-Saharan Africa, will improve little. The paper also presents a more pessimistic scenario brought about by cuts in investment in agriculture and a more hopeful scenario based on increased investment.